Rational expectations and inflation - Sargent, Thomas J. (Princeton University Press, 2013)
This collection of essays uses the lens of rational expectations theory to examine how governments anticipate and plan for inflation, and provides insight into the pioneering research for which Thomas Sargent was awarded the 2011 Nobel Prize in economics. Rational expectations theory is based on the simple premise that people will use all the information available to them in making economic decisions, yet applying the theory to macroeconomics and econometrics is technically demanding. Here, Sargent engages with practical problems in economics in a less formal, noneconometric way, demonstrat.